Flavopiridol Protects Bone Tissue by Attenuating RANKL Induced Osteoclast Formation - Hu, Zi’ang; Chen, Yilei; Song, Lijiang; Yik, Jasper H. N.; Haudenschild, Dominik R.; Fan, Shunwu (Frontiers in Pharmacology, 2018)
Bone resorption and homeostasis is carried out by osteoclasts, whose differentiation and activity are regulated by the RANK/RANKL axis. Our previous studies using a mouse model of joint injury show that joint trauma induces local inflammation followed by bone remodeling. The transcription factor cyclin-dependent kinase 9 (CDK9) is the major regulator of inflammation, as CDK9 inhibitor flavopiridol effectively suppress injury-induced inflammatory response. The objective of this study was to investigate the underlying mechanism through which flavopiridol regulates bone resorption. The effects of CDK9 inhibition, by the specific-inhibitor flavopiridol, on bone resorption were determined in vivo using two distinct and clinically relevant bone remodeling models. The first model involved titanium particle-induced acute osteolysis, and the second model was ovariectomy-induced chronic osteoporosis. The effects and mechanism of CDK9 inhibition on osteoclastogenesis were examined using in vitro culture of bone marrow macrophages (BMM). Our results indicated that flavopiridol potently suppressed bone resorption in both in vivo bone-remodeling models. In addition, CDK9 inhibition suppressed in vitro osteoclastogenesis of BMM and reduced their expression of osteoclast-specific genes. Finally, we determined that flavopiridol suppressed RANKL signaling pathway via inhibition of p65 phosphorylation and nuclear translocation of NF-κB. Summary, CDK9 is a potential therapeutic target to prevent osteolysis and osteoporosis by flavopiridol treatment.